2022
DOI: 10.1038/s41598-022-16135-0
|View full text |Cite
|
Sign up to set email alerts
|

Risk trajectories of complications in over one thousand newly diagnosed individuals with type 2 diabetes

Abstract: Although the increased risk of complications of type 2 diabetes (T2D) is well known, there is still little information about the long-term development of comorbidities in relation to risk factors. The purpose of the present study was to describe the risk trajectories of T2D complications over time in an observational cohort of newly diagnosed T2D patients, as well as to evaluate the effect of common risk factors on the development of comorbidities. This national cohort study investigated individuals with T2D i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This suggests that patients with early-onset T2D have higher overall lipid levels, many are borderline hyperlipidemia, and may progress to hyperlipidemia more quickly in the future, which explains our main findings. A study of the risk trajectory of T2D complications found that the cumulative incidence of CVD increases with age in the T2D population [ 30 ], the higher prevalence of CVD risk in late-onset T2D may be because age as a risk factor for CVD risk is more pronounced in lat-onset patients in our study. Regarding medication use patterns, the results of a case‒control study indicated that there was a higher rate of antihypertensive medication use at diagnosis in late-onset T2D [ 31 ], which is consistent with our result in which patients with late-onset T2D had a higher rate of hypertension prevalence.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…This suggests that patients with early-onset T2D have higher overall lipid levels, many are borderline hyperlipidemia, and may progress to hyperlipidemia more quickly in the future, which explains our main findings. A study of the risk trajectory of T2D complications found that the cumulative incidence of CVD increases with age in the T2D population [ 30 ], the higher prevalence of CVD risk in late-onset T2D may be because age as a risk factor for CVD risk is more pronounced in lat-onset patients in our study. Regarding medication use patterns, the results of a case‒control study indicated that there was a higher rate of antihypertensive medication use at diagnosis in late-onset T2D [ 31 ], which is consistent with our result in which patients with late-onset T2D had a higher rate of hypertension prevalence.…”
Section: Discussionmentioning
confidence: 60%
“…The results of previous studies, as well as ours, have indicated a more severe metabolic disorder in early-onset type 2 diabetes, both in general characteristics and treatment patterns. A cohort study conducted in Sweden described the cumulative incidence and risk factors for comorbid diseases for newly diagnosed T2D patients, but they didn’t evaluate the progression of hypertension or hyperlipidemia and the difference between early-onset and late-onset T2D [ 30 ]. One study showed that patients with early-onset diabetes are more likely to have combined hyperlipidemia [ 31 ], and another study of 1,421 cases revealed that patients with early-onset T2D had higher triglycerides (TG) and glycated hemoglobin (HbA1c) [ 32 ], all of which suggest that patients with early-onset diabetes are clinically characterized by metabolic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…By the time of diagnosis, patients may have already developed some diabetic complications. Previous studies have shown that diabetic kidney disease (DKD) has the highest prevalence among diabetic complications when type 2 diabetes mellitus is diagnosed 2,3 . DKD is also a leading cause of diabetes-related cardiovascular disease and mortality 4 , resulting in high medical costs and healthcare burdens.…”
Section: Introductionmentioning
confidence: 99%